2022
DOI: 10.3390/su15010434
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between MICP-Based Bio-Cementation Versus Traditional Portland Cementation for Oil-Contaminated Soil Stabilisation

Abstract: In recent years, oil spills and leakages have often occurred during oil exploration, transportation, handling, usage, and processing, causing serious global environmental problems. Microbially-induced carbonate precipitation (MICP) is an emerging green, environmentally friendly, and sustainable technology that has proven to be a promising alternative for soil stabilisation. This paper provides a comparison between the mechanical performance of oil-polluted sand treated with biocement and traditional Portland c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The difference in stiffness between bio-cemented samples and Portland-cemented samples could potentially be attributed to the degradation of the weaker bonds between calcite and sand, finally leading to its breakage into fine particles that subsequently fill the internal voids. Yin et al [45] also found that the stress-strain curve of the Portland cement-treated sample showed higher values of stiffness compared to those of bio-cemented samples. Another reason for the enhanced strength and stiffness observed in the samples treated with ordinary Portland cement (OPC) can be attributed to the process of cement hydration, which continues for up to 28 days following the initial reaction between the cement and the soil [39].…”
Section: Failure Mode and Stiffnessmentioning
confidence: 96%
“…The difference in stiffness between bio-cemented samples and Portland-cemented samples could potentially be attributed to the degradation of the weaker bonds between calcite and sand, finally leading to its breakage into fine particles that subsequently fill the internal voids. Yin et al [45] also found that the stress-strain curve of the Portland cement-treated sample showed higher values of stiffness compared to those of bio-cemented samples. Another reason for the enhanced strength and stiffness observed in the samples treated with ordinary Portland cement (OPC) can be attributed to the process of cement hydration, which continues for up to 28 days following the initial reaction between the cement and the soil [39].…”
Section: Failure Mode and Stiffnessmentioning
confidence: 96%
“…The traditional method of cementing soil particles involves the mixing of Portland cement and soil to create a soil-cement. The manufacture of Portland cement contributes to global warming through the release of CO 2 [1][2][3]. Producing one tonne of Portland cement releases roughly one tonne of CO 2 into the atmosphere; the cement industry accounts for seven to eight percent of human-produced CO 2 emissions [4].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical process, as reported by De Belie [17], is outlined in Equations ( 1)- (6). Active ureolytic bacteria produce urease enzyme, which catalyses the hydrolysis of urea, resulting in the production of carbamate (NH 2 COOH) and ammonia (NH 3 ), as per Equation (1). Carbamate spontaneously hydrolyses to produce ammonia and carbonic acid (Equation ( 2)).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional MICP grouting methods exhibit low efficiency, and achieving a higher strength curing effect typically requires multiple grouting, making the process cumbersome [22,23]. Researchers have addressed this issue by optimizing grouting materials and methods, such as injecting a small amount of calcium chloride solution as a bacterial fixative solution [24,25], carrying out single-phase grouting by adjusting temperature or pH [26,27], optimizing crystallization sites by adjusting saturation [28], and adding fibers [29].…”
Section: Co(nhmentioning
confidence: 99%